(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to know the effect of teaching using systemic thinking skills in the direction towards mathematics among female students in the fourth scientific grade. The usual method, and the attitude towards mathematics scale was built along the lines of the three-point Likert scale, and it consisted of ((30 items), and its validity and reliability were verified, and the test formula was used